1992
DOI: 10.1103/physreva.46.3555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intermediate radicals in theCH4microwave plasma by theLi+

Abstract: We (i) describe the complete Li -adduct mass spectrum of the CH4 microwave discharge plasma, obtained by ion attachment techniques, (ii) give evidence that many radicals are produced in the plasma, and (iii) present a preliminary spectral identification analysis. The identified species are C"Hz" (n =2-13), C"Hz"+l (n =2-13), C"H"(n =2,4, 5, 6), and so on. PACS number(s): 52.80.s, 35.20.WgIn order to demonstrate that a recent development of the Li+ ion attachment and quadrupole mass spectrometer technique for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20] Highlights of the results from the above attempts are briefly summarized here.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19][20] Highlights of the results from the above attempts are briefly summarized here.…”
Section: Applicationsmentioning
confidence: 99%
“…With the aim of developing a more efficient and sensitive technique for detecting intermediate radical species in chemical reactions, Fujii has proposed 10 and developed [11][12][13][14][15][16][17][18][19][20] a novel method based on soft ionization Li ϩ ion attachment mass spectrometry (Li ϩ MS). The experimental details, operation, and unique features of a Li ϩ MS system are presented in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and evaluation of HC radicals in discharge plasma has been investigated by a variety of techniques [3][4][5][6][7]. Kojima et al [3] have reported the direct observation of methyl radicals using threshold ionization mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Rudolph and Moore [5] measured mass spectra of free radicals from a microwave discharge in a fast flow of methane in argon and in hydrogen and reported the presence of many HC radicals, such as C 2 H 5 , C 3 H 3 , C 3 H 7 , C 4 H 5 , C 5 H 7 , C 5 H 9 , and C 5 H 11 . Fujii [6,7] examined methane microwave discharge plasmas using the Li + MS technique and detected longer-chain HC free radical species, such as C n H 2nÀ1 and C n H 2n+1 (n = 1-8), along with a few aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…ion-attachment mass spectrometric (IAMS) method [10][11][12][13][14]. IAMS is unique in that it provides only Li ?…”
Section: Introductionmentioning
confidence: 99%